2014
DOI: 10.1080/07373937.2013.879593
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Electrical Conductivity as a Quality Parameter of Lemongrass Leaves (Cymbopogon citratusStapf) Submitted to Drying Process

Abstract: This study aims to evaluate the quality of lemongrass plants after drying at different speeds (1.0, 1.5, 2.0 m s À1 ), temperatures (40, 50, 60, and 70 C), and drying air control systems (manual and automatic) using electrical conductivity as a parameter for evaluation. Firstly, we evaluated the time necessary for imbibitions of material in deionized water after drying for different air speeds and control systems. Secondly, the effect of temperature in fresh and dry plants was evaluated, comparing them with c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 35 publications
7
22
0
Order By: Relevance
“…Increasing the drying temperature and time led to greater cell damage to the grain tissues, according to results reported by other authors (Oliveira et al, 2013;Coradi et al, 2014). However, the wetting was not an intensive increase in electrical conductivity.…”
Section: Resultssupporting
confidence: 74%
See 2 more Smart Citations
“…Increasing the drying temperature and time led to greater cell damage to the grain tissues, according to results reported by other authors (Oliveira et al, 2013;Coradi et al, 2014). However, the wetting was not an intensive increase in electrical conductivity.…”
Section: Resultssupporting
confidence: 74%
“…The loss of grain quality due to the leaching of ions was verified through the electrical conductivity, that is, the rewetting of the grains contributed to the reduction in quality, in proportions similar to those in the drying. However, higher electrical conductivity values coincided with the higher temperature treatments, because these conditions promoted largest amount of leached ions, i.e., greater disruption of cell membranes of the tissues that make up the grains (Vieira, 2008;Siqueira et al, 2011;Coradi et al, 2014). Thus, it can be seen that increased water content in the grains for the allowed marketing conditions (13.5% w.b.)…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…), causing a chain of random undesirable reactions. According to CORADI et al (2014a), once cell disruption is observed, those reactions become irreversible, resulting in a product of poorer quality at the end of the process.…”
Section: Data Analysis Inmentioning
confidence: 99%
“…For storing and selling, moisture content of soybeans must not exceed 14%, or even 12%, because it would improve storage quality. Therefore, drying process is extremely important; however, it may damage grains for changing their physical properties or even causing direct damage thereto NIAMNUY et al, 2011;SOUSA et al, 2011;CORADI et al 2014a). Even though the mechanical drying of soybeans can anticipate harvest, the high air temperatures involved in such process may cause biochemical changes in the product, affecting its quality.…”
Section: Introductionmentioning
confidence: 99%